Nanomaterial solidification inside the storage system by means of finite element method. (15th August 2023) - Selim, Mahmoud M.; Alrkyan, Rakan A.I.; Saidan, Bader H.A.; Musa, Awad
Abstract: To reduce the required time for solidification, the system of present study has been combined with fin. The testing base material was mixed with water to generate homogeneous mixture with higher conductivity. The numerical procedure for modeling this unsteady process has been validated and influence of loading nanoparticles has been evaluated. The impact of diameter of powders on treatment of system has been involved with considering conductivity of nanomaterial as function of this parameter. The style of mesh was adapted with location of ice front. As diameter of powders declines from 50 to 40 and 30, the required time firstly decreases 49.25 % then it increases about 24.99 %. Loading nanoparticles with higher concentration can reduce the time of process about 41.22 %. The impact of concentration for middle level of diameter is more sensible. Highlights: To reduce the required time for discharging, new design was offered. The impact of diameter of powders on treatment of system was scrutinized. Loading nanoparticles can reduce the time of process about 41.22 %.